Optimization Strategy for Digital Transformation and Communication to Improve Employee Performance at Sekopi Denpasar - Tariana, I Wayan Aditya; Cakraningrat, Putu Bagus Wichitakani Wahyu (Pasundan Social Science Development, 2024)
This research examines the optimization strategy for digital transformation and communication to enhance employee performance at Sekopi Denpasar. In the face of rapid technological advances and a shifting business landscape, companies must adapt and optimize their internal processes to maintain competitiveness. Digital transformation and effective communication are key drivers in this adaptation process, influencing productivity, employee satisfaction, and overall organizational success. This study employs a qualitative descriptive approach to explore how Sekopi Denpasar has implemented digital strategies and communication improvements to optimize employee performance. Data was collected through interviews, observations, and documentation analysis, focusing on employees’ experiences with digital tools, communication channels, and their perceived impact on job performance. The findings reveal that a well-executed digital transformation strategy, alongside strong communication practices, leads to a more engaged and efficient workforce. Challenges in the process, including resistance to change and the need for continuous training, are also highlighted. The study suggests that companies like Sekopi Denpasar must focus on building a culture of innovation and transparency, fostering collaboration, and ensuring that digital tools align with employees' needs to maximize their potential. The research contributes to the growing body of knowledge on the intersection of digital transformation, communication, and employee performance, offering valuable insights for organizations seeking to thrive in a digital-first world.